2019
DOI: 10.3390/jof5030070
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Infection with Histoplasma capsulatum

Abstract: Histoplasmosis is an endemic fungal infection that may affect both immune compromised and non-immune compromised individuals. It is now recognized that the geographic range of this organism is larger than previously understood, placing more people at risk. Infection with Histoplasma capsulatum may occur after inhalation of conidia that are aerosolized from the filamentous form of the organism in the environment. Clinical syndromes typically associated with histoplasmosis include acute or chronic pneumonia, chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 43 publications
(80 reference statements)
0
34
0
Order By: Relevance
“…When the CNS involvement is not known, transition from L-Amb to itraconazole, and then itraconazole interruption may be accelerated, thus leading to suboptimal treatment of the CNS infection. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the CNS involvement is not known, transition from L-Amb to itraconazole, and then itraconazole interruption may be accelerated, thus leading to suboptimal treatment of the CNS infection. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas the relapse rate and mortality of CNS histoplasmosis used to be very high 5 —often presenting as meningitis in severely immunocompromised patients with poor compliance—antifungal therapy has transformed this universally fatal illness to a manageable condition, if diagnosed and treated early. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, visual disturbances in CNS histoplasmosis are rare, with an incidence below 10%, as stated in the largest multicenter retrospective study to date by Wheat et al [7] Most neurological manifestations were reported to be transient, lasting for less than one week in a quarter of the cases. Therefore, high index of suspicion and a prompt diagnosis are critical, as the CNS compromise not only increases morbidity, mortality and the risk of relapse, but also dictates a more aggressive and longer course of treatment [4] , [7] , [8] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…False positives and cross-reactions can happen with blastomycosis, paracoccidioidomycosis, cryptococcosis, and penicilliosis [24] , [25] . Additionally, fungal culture of the CSF is a lengthy and poorly sensitive process and is therefore best used as a confirmatory test rather than diagnostic [6] , [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation